El Karaoke como recurso didáctico para mejorar la producción oral del idioma Inglés de los estudiantes del V ciclo de la escuela académico profesional de idiomas de la UNSM Tarapoto - 2013 - Leon Suarez, Ana Ruth (2013)
The present work gives a new alternative in the teaching-learning of the English language with the purpose of improving the oral production of the students of the National University of San Martin - Tarapoto, Professional Academic School of Languages. The research had as a principal objective to develop the oral production of the English language through the methodological proposal Let's Sing and Learn English Together that used as a main strategy the KARAOKE, as an educational resource that was carried out in 8 lesson plans. Each class has 4 stages: Music to my ears, All ears, Face the music and a toast. We could appreciate the achievement of the students in each class making use of observation sheets that were checked and organized correctly. In order to achieve the goals, the methodological proposal Let's Sing and Learn English Together was applied, then a data tabulation, the description and the corresponding analysis were performed, we compared the data obtained before and after performing the proposal, which assessed four components: fluency, coherence, intonation and vocabulary. The results show that the methodological proposal Let's Sing and Learn English Together influenced significantly in the development of oral production in the students of the V cycle of the Professional Academic School of Languages-UNSM. So it is clear that the methodology, content and materials used in the application of the methodological proposal Let's Sing and Learn English Together influenced significantly in the oral production of the English language students of the V cycle of the Professional Academic School of Languages of the National University of San Martin.